PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT EFARINA PANGKALAN KERINCI - , Rosnelly Roesdi, Rahma Dani , Jumiati Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This research was conducted at Efarina Hospital Pangkalan Kerinci. The purpose of this study was to determine whether work motivation, work environment, and work stress affect nurse performanceat Efarina Hospital Pangkalan Kerinci. The population in this study were all nurses at Efarina Hospital Pangkalan Kerinci with a total of 76 employees. The sampling technique method uses a saturated sample method, namely as many as 76 respondents. Technical analysis for test hypothesis that used in this study are double regression. using descriptive statistical analysis and simple linear regression analysis to produce classical assumption tests, data analysis models, coefficient of determination and prove hypotheses. The of this study indicate that the variable of work motivation has a positive and significant effect on the performance of nurses, the work enviroment variable has a positive and significant effect on the performance of nurses and work stress has a negative and significant effect on the performance of nurses. Work motivation, work environment and work stress simultaneously affect the performance of nurses. Keywords: Work Motivation; Work Environment; Work Stress;  Performance